FACTORS THAT RELATED TO THE MENSTRUAL CYCLE ON CONTRACEPTIVE INJECTION USERS IN THE DISTRICT OF PUSKESMAS SETU 1 IN 2023 - Dalila Eka Saffanah; Mizna Sabila; Rusman Efendi; Luqman Effendi (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Significant population growth can have an impact on several things, such as malnutrition that cannot be handled, and some social facilities that are not yet qualified. One of the ways to control population growth is through the KB (birth control) program. However, the use of KB can trigger health problems such as disturbances or changes in the menstrual cycle. This research is quantitative research with analytical methods and used cross-sectional as the study design. The sample for this study was 64 KB acceptors in the District of Puskesmas Setu 1, who were taken using the Probability Proportionate to Size (PPS) technique. Based on the analysis test, there were 4 out of 5 independent variables that correlated with the menstrual cycle, there is nutritional status (p-value 0.010); duration of use (p-value 0.003); re-use compliance (p-value 0.000), while the age variable does not correlate with the menstrual cycle (p-value = 0.755). There is a significant correlation between variables, that is nutritional status, duration of use, and re-use compliance. Suggestions for KB acceptors is to always consult with experts regarding appropriate contraception and the long-term effects that are likely to be obtained.